PENGARUH ENERGI TERBARUKAN, EMISI KARBON, DAN FOREIGN DIRECT INVESTMENT TERHADAP PERTUMBUHAN EKONOMI NEGARA ANGGOTA OKI - Nadira Rahmandani; Eka Puspa Dewi (ITB AAS INDONESIA Surakarta, 2023)
Climate change is currently an important topic to talk about. Member countries of the Organization of Islamic Cooperation are one of the regions of the country that are vulnerable to climate change due to high exposure and low adaptive capacity. This study aims to determine the effect of renewable energy, carbon emissions, and FDI on economic growth for two groups of low-income and middle-income OIC countries. Data is obtained from the World Development Indicators for the period 2000-2015. This study uses panel data analysis techniques. The result show that simultaneously renewable energy, carbon emissions and FDI have a significant effect on economic growth for both group. Partially for both group, the empirical study found that renewable energy had a significant negative effect on economic growth. Carbon emissions have a significant positive effect on economic growth, while FDI only has a significant effect for the middle-income group of OIC countries. This finding can be a suggestion for the OIC to continue encouraging the energy transition while taking into account the economic conditions of these countries.